The policy of import substitution as the basis for economic security and well-being of society - Makasheva Yu. S. Yuliya Sergeevna; Makasheva N. P. Nataliya Petrovna; Gromova A. S. Anna Sergeevna; Andreeva N. V. Natalia Viktorovna; Ishtunov S. A. (Petroleum Engineering Economics and Mining Law, 2016)
Title screen